Autism associated to a deficiency of complexes III and IV of the mitochondrial respiratory chain. - José Guevara Campos1, José Guevara Campos1; González Guevara, Lucía; Briones, Paz; López Gallardo, Ester; Bulán, Nuria; Ruiz Pesini, Eduardo; Ramnarine, Denisse; Montoya, Julio (Investigación Clínica, 2013)
Â  Autism is the prototype of generalized developmental disorders or what today are called autism spectrum disorders. In most cases it is impossible to detect a specific etiology. It is estimated that a causative diagnosis may be shown in approximately 10-37% of the cases, including, congenital rubella, tuberous sclerosis, chromosome abnormalities such as fragile X syndrome and 22q13.3 deletion syndrome, Angelman, Williams, Smith-Magenis, Sotos, Cornelia de Lange, M í¶bius, Joubert and Goldenhar syndromes, Ito”™s hypomelanosis, as well as certain cerebral malformations and several inherited metabolic disorders. The case of a 3-year old girl is described, who was considered as autistic according to the criteria established by the DSM-IV manual for psychiatric disorders. She showed a delay in psychomotor development since she was 18 months old; she pronounces very few words (10), points to some objects, does not look up and it is hard to establish eye con- tact with her. She has paradoxical deafness and therefore, does not respond when called or when she is given orders, she is beginning to walk. She has not convulsions. Laboratory tests showed an anion gap of 31.6 mEq/L, lactate: 2.55: mmol/L, pyruvate: 0.06 mmol/L, and elevated lactate to/pyruvate ratio: 42.5. Under optical microscopy a muscular biopsy showed a reduction of the diameter of muscular fibers. The study of energy metabolism showed a partial deficiency of complexes III and IV of the respiratory chain, which allowed us to conclude that this was a mitochondrial dysfunction with an autistic clinical spectrum.